Bleeding from Small Intestine: No Man's Land - Sahakian, Ara; Lee, Sang W.; Shin, Joongho (Clinics in Colon and Rectal Surgery, 2020)
Bleedings from small intestine account for 5% of all gastrointestinal bleeding. With advanced endoscopic tools, such as video capsule endoscopy and deep enteroscopy, accurate diagnosis and treatment is possible in majority of cases with low mortality and morbidity. Nonoperative management includes endoscopic hemostasis and angiographic embolization. Recurrence after initial treatment is relatively common. Surgery is reserved for the cases that are refractory to endoscopic or angiographic treatment, bleeding from tumor or mass lesions, or hemodynamic instability. At the time of surgical exploration, unless the lesion has been marked by endoscopic tattoo or clip, intraoperative enteroscopy is often necessary to localize the lesion.
Keywords: video capsule endoscopy (VCE); deep enteroscopy; intraoperative enteroscopy